A Method for Locating the Real Roots of the Symbolic Quintic Equation Using Quadratic Equations. Issue 7 (20th May 2022) - Prodanov, Emil M.
Abstract: A method is proposed with which the locations of the roots of the monic symbolic quintic polynomial x 5 + a 4 x 4 + a 3 x 3 + a 2 x 2 + a 1 x + a 0 x^5 + a_4 x^4 + a_3 x^3 + a_2 x^2 + a_1 x + a_0 can be determined using the roots of two resolvent quadratic polynomials: q 1 ( x ) = x 2 + a 4 x + a 3 q_1(x) = x^2 + a_4 x + a_3 and q 2 ( x ) = a 2 x 2 + a 1 x + a 0 q_2(x) = a_2 x^2 + a_1 x + a_0, whose coefficients are exactly those of the quintic polynomial. The different cases depend on the coefficients of q 1 ( x ) q_1(x) and q 2 ( x ) q_2(x) and on some specific relationships between them. The method is illustrated with the full analysis of one of the possible cases. Some of the roots of the symbolic quintic equation for this case have their isolation intervals determined and, as this cannot be done for all roots with the help of quadratic equations only, finite intervals containing 1 or 3 roots, or 0 or 2 roots, or, rarely, 0, or 2, or 4 roots of the quintic are identified. Knowledge of the stationary points of the quintic lifts this indeterminacy and allows finding the isolation interval of each root. Separately, using the complete root classification of the quintic, one can also lift this indeterminacy. The method also allows to see how variation of the individual coefficients of the quintic affect its roots. No root finding iterations or any numerical approximations are used and no equations of degree higher than two are solved. Abstract : The isolation intervals of the roots of the parametric quintic polynomial x 5 + a 4 x 4 + a 3 x 3 + a 2 x 2 + a 1 x + a 0 x^5 + a_4 x^4 + a_3 x^3 + a_2 x^2 + a_1 x + a_0 are determined geometrically by the roots of two auxiliary quadratic polynomials: x 2 + a 4 x + a 3 x^2 + a_4 x + a_3 and a 2 x 2 + a 1 x + a 0 a_2 x^2 + a_1 x + a_0 . This graph is an example for the case with a 4 > 0 a_4 > 0, a 3 < 0 a_3 < 0, a 2 > 0 a_2 > 0, a 1 < 0 a_1 < 0 .